Display of national identity in modern Palestinian literature - Д.Т., Коптилеуова; А.Е., Жумадилова (Journal of Oriental Studies, 2020)
In the first half of the twentieth century, Palestine was shocked by serious political, social, and literary changes. The writers felt the need for a new type of literary work that could capture and express current historical events and circumstances, as well as in order to move towards change. Literature has become a kind of barometer of the mood of the nation. With the beginning of the new century and the change in the political situation in the country, the Palestinian national identity undergoes changes, losing its sharp political color, which was also reflected in literature. The writers’ thoughts are not only ideas about national independence, political freedom, they give way to topics such as economic life: wealth and poverty, the labor market, consumer protection, as well as women’s freedom, political and ideological contradictions. The article discusses the main meanings of the concepts of “identity”, “national identity”, and their reflection in the works of young Palestinian writers such as Ziyad Khaddash, Jamal al-Qawasmi, Ibtisam Azem, as well as in the work « في حضرة الغياب » (“In the Presence of Absence”) of the classic of Palestinian literature, Mahmoud Darwish, in the context of the Palestinian-Israeli conflict. The main aspects of national identity are highlighted in the discourse of prose works of these writers. Key words: national identity, Palestine, Israel, new generation, new subjects, alienation, homeland.